A Stepwise Approach to Systematic Reviews and Meta-analyses of Endovascular Interventions. (October 2020) - Antoniou, George A.; Biondi-Zoccai, Giuseppe; Versaci, Francesco; Antoniou, Stavros A.
The accrual of clinical studies poses important challenges to researchers and practitioners, especially in the field of endovascular therapy, where patient, lesion, technique, and device subtleties abound. Systematic reviews and meta-analyses may prove particularly fruitful in such settings by increasing statistical precision and bolstering external validity if the evidence base on a specific topic is consistent or by highlighting important discrepancies in the opposite scenario. However, mastering the correct approach to systematic review and meta-analysis is challenging for careful readers or for those interested in conducting such an evidence synthesis exercise. The present article highlights a stepwise approach to systematic reviews and meta-analyses, focusing on endovascular interventions, which will prove useful to anyone reading or wishing to synthesize the evidence base on endovascular topics to optimize decision making or shape future research efforts.